A reversible fluorescent-colorimetric imino-pyridyl bis-Schiff base sensor for expeditious detection of Al3+ and HSO3− in aqueous media1. Issue 29 (7th August 2015) - Ghorai, Anupam; Mondal, Jahangir; Chandra, Rukmani; Patra, Goutam K.
<x xml:space="preserve">Abstract</x> A reversible fluorescent-colorimetric imino-pyridyl bis-Schiff base receptor (N1E, N4E)-N1, N4-bis(pyridine-4-ylmethylene)benzene-1, 4-diamine (L) for easy, convenient, rapid and sensitive detection of both Al3+ and HSO3− in aqueous medium has been developed.